Live and Let Die: On the Management of Creativity - Michael Hartmann; Désirée Laubengaier; Kai Foerstl (Technology Innovation Management Review, 2019)
Literature has pointed to the importance of feedback on creative ideas in innovation management processes. However, little is known about the practices that constitute the feedback process and their effect on employees’ future willingness to consistently and recurrently contribute with creative ideas to organized innovation management efforts. In this research, we draw on data from a single case study at a German multinational manufacturing firm. We show the flip side of managerial attempts to provide feedback and foster employees’ creative output. In particular, we identify distinct practices organizational actors employ along the sequence of idea generation, elaboration, championing, and implementation, and find that the practices can turn organized innovation management efforts into a political process. Furthermore, we present a virtuous and a vicious circle of managerial attempts to manage creativity in innovation processes. In doing so, we highlight the value of taking a practice lens to better understand the challenges in organized innovation management efforts and propose future research in other contexts. We suggest that managers should flexibly design organized innovation management processes to account for radical ideas and to pay close attention to a coherent communication when providing feedback and encouraging employees to contrive creative ideas. Our work contributes to the body of research on innovation management by shedding light on the dark side of organized innovation management efforts.